IMPLEMENTATION OF ANALYTICAL HIERARCHY PROCESS TO CHOOSE RISK MITIGATION PLAN FOR CO-LIVING SPACE DEVELOPMENT PROJECT - Teuku Muhammad Abidzar Saddam; Taufik Faturohman (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study comprehensively assesses and proposes mitigation strategies for critical risks within a specific co-living development project in Haji Nawi, set against the backdrop of Jakarta's increasing housing deficit. The research integrates the ISO 31000:2018 risk management framework, supplemented by PESTLE, VRIO, and SWOT analyses for environmental scanning. Its primary objective is to identify, accurately measure, prioritize, and formulate actionable mitigation plans for significant project threats. Qualitative data gathered from expert interviews and focused group discussions informed the risk assessment process. The study identified 37 distinct potential risks, categorized into Strategic, Financial, Operational, Legal & Compliance, and Reputational domains. Through rigorous measurement and prioritization aligned with the development firm's risk appetite, 11 risks were classified as High to Extreme, demanding urgent treatment. The Analytical Hierarchy Process (AHP) was then applied to evaluate and select the most suitable mitigation plans for the three highest-priority, extreme risks: Permit Delay, Community Rejection, and Contractor Failure. Results strongly recommend implementing Contingency Buffers in Project Timelines for Permit Delay. The Establishment of a Grievance Redress Mechanism emerged as the preferred strategy for Community Rejection, while Collaborative Contract Models (e.g., Alliancing) proved optimal for mitigating Contractor Failure. This research provides a robust framework and data-driven recommendations, crucial for ensuring project stability and success in dynamic urban property markets.